Clinical and angiographic profile of patients undergoing Primary angioplasty in acute myocardial infarction in a tertiary care center in rural India - Dr. Vaibhav Anil Patil, Dr. Sumit Rameshwar Sejol, Dr. Vivek Divakar Chaudhari, Dr. Ansari Bashiruddin, Dr. Harshal Surendra Patil (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Acute myocardial infarction (AMI) is a leading cause of morbidity and mortalityworldwide. Primary angioplasty is a definitive intervention for AMI, but its profile varies across diverse populations.